Household Waste Management Education for Dengue Fever Prevention in Murtigading Bantul - Sulistyawati, Sulistyawati (Institut Teknologi dan Bisnis Asia Malang, 2024)
Purpose: This study investigates the impact of household waste management education on Dengue Hemorrhagic Fever (DHF) prevention in Murtigading, Bantul. It highlights the significance of improper waste disposal as a risk factor for dengue transmission. Method: Educational lectures were conducted for residents in targeted areas (Ngentak, Pucanganom I, Trisigan I). Data on community knowledge of waste management were collected and analyzed to assess the intervention's effectiveness. Practical Applications: The findings inform public health efforts to prevent DHF by improving community awareness of proper waste management. Similar education programs can enhance disease prevention and community health.Conclusion: Community knowledge regarding waste management remains insufficient, highlighting the ongoing need for education and awareness initiatives. Continued efforts to improve community understanding of proper waste disposal practices are essential in combating dengue transmission and reducing the incidence of DHF.